Strategi Pemasaran Online Untuk Meningkatkan Minat Beli Konsumen Produk Makanan Dan Minuman UMKM Di Kota Bogor - Ruhiyat, Dadang; Sulaeman, Ahmad; Purnawati, Rini (Institut Pertanian Bogor, 2023)
Online marketing has sparked consumers' interest to make purchases to satisfy their various needs, including food and beverages. Several factors are believed to strongly influence consumers’ buying interest in online marketing, including: price, advertising and product quality and payment security. This study aims to provide suggestions and recommendations for online marketing strategies to MSMEs in the food and beverage sector to further increase consumer buying interest. The research is conducted by identifying consumer behavior and analyzing the influence of 4P marketing variables, i.e., price, sales promotion and product quality and payment security for consumers purchasing MSME food and beverage products online. Data collection was done through questionnaire and interviews with 106 food and beverage consumers and 40 MSMEs located in Bogor city, using purposive sampling. The analytical method used in this research is descriptive qualitative and quantitative analysis. The results of multiple linear regression analysis can be summarized as follows: First, product, price, promotion and payment security variables have a significant influence on the variable of consumer buying interest in food and beverages. Second, variables that influence online purchase interest include: promotions, products, and payment security, while prices do not really influence consumers’ purchase interest in online marketing. The results of Strength, Weakness, Opportunity & Threat (SWOT) of the most appropriate strategy that can be applied is S-O (Strength-Opportunity). The results of the Quantitative Strategic Planning Matrix (QSPM) analysis achieved the highest Total Attractive Score (TAS) score by innovating products based on consumer needs on the basis of consumer desires and also in accordance with people's purchasing power.